Half sphere and single clip-bar retained implant supported silicone auricular prosthesis - Saumya Kapoor; Saumyendra Vikram Singh; Deeksha Arya (Journal of Oral Biology and Craniofacial Research)
Implant supported auricular prosthesis can be retained by several mechanical means, one of them being the Hader bar and clip system. Conventionally two or more rider clips are used. This technique describes a modified Hader bar design to maintain retention while eliminating the requirement of a second clip, significantly bringing down cost.